Molecular Dynamics study on size dependencies of melting dynamics in Gold thin film. Issue 6 (March 2021) - Fahdiran, R; Sugihartono, I; Handoko, E; Budi, E; Susila, A B; Prayitno, T B; Sunaryo, S
Abstract: We explore the size dependencies of melting dynamics of Gold in the form of thin film. The sizes are 4.896 nm, 7.344 nm and 9.792 nm which is comparable between nanoparticle diameter and thin film thickness. The systems are treated by increasing temperature from 300 K to 1400 K. Molecular Dynamics (MD) scheme is employed to follow the trajectories of the systems up to 20 ps. Structure factor analysis indicated that the melting is suppressed by the increasing size.